Psychological well-being of refugee children - Ajduković, Marina (Array, 1993)
Two groups of refugee families participated in a program aimed at preventing children’ s mental health problems. The program attempted to gain insight into character and scope of problems of refugee families and to develop and implement a spectrum of interventions that would meet their specific psychological needs. Data about the family situation and the psychosocial adaptation of refugee children to displacement was gathered during detailed structured interviews with the mothers, while the study families were accommodated either in a shelter or with host families. A considerable range of stress-related reactions among displaced children were identified (e.g., sleeping and eating disorders, separation fears, and withdrawal or aggression). Refugee children exhibited a significantly higher incidence of stress reactions if their mothers had difficulty coping with the stress of displacement. The findings also indicated that children in the collective shelter were at greater mental health risk than their peers housed with host families.